Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."– Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Au temps de l’homonationalisme: mythologie nationaliste et inclusivité LGBT - Glenn, Clinton (esse arts + opinions, 2017)
À travers cette rhétorique homonationale, l’exceptionnalisme canadien met en place tous les éléments pour récupérer la sexualité queer racisée (blanche et non blanche) selon un mode de gouvernance néolibéral faisant fi de la couleur en produisant des sujets citoyens queers exceptionnels et en affirmant le statut exceptionnel du Canada dans le monde.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; arts; canada; cours; discipline; har4600; histoire de l'art; histoire et politique; homonationalisme; identités LGBTQIA2+; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; thématiques; ville

Au-delà du plaisir visuel: féminisme, énigmes, cinéphilie - Mulvey, Laura (Éditions Mimésis, 2017)
En 1975, Laura Mulvey publie Plaisir visuel et cinéma narratif, texte polémique qui met en lumière la manière dont la forme filmique serait structurée par l’inconscient de la société patriarcale. C’est l’essai fondateur des études féministes sur le cinéma. Rédigés entre 1975 et 2011, les textes choisis dans ce volume sont marqués par la redécouverte féministe de la psychanalyse et les transformations induites par le développement des technologies numériques. Qu’elle s’attache à des genres ou à des auteurs incontournables (le western, le mélodrame, Ophüls, Hitchcock, Godard), qu’elle incarne l’avènement d’un « spectateur pensif », qu’elle analyse les paradoxes de l’esthétique hollywoodienne ou la compilation de films de propagande coloniale, Laura Mulvey fait preuve d’une cinéphilie active et engagée.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; cinema hollywoodien; cinéma; com5170; communication; corps; cours; discipline; discours dominant; europe; har4600; histoire de l'art; histoire et politique; male gaze; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; regard masculin; royaume-uni; régions géographiques; sofia; systèmes d'oppressions; thématiques; théorie du cinéma; états-unis